PROTEIN KINASE A AND Epac ACTIVATION BY cAMP REGULATES THE EXPRESSION OF GLIAL FIBRILLARY ACIDIC PROTEIN IN GLIAL CELLS - Sugimoto, Naotoshi; Miwa, Shinji; Nakamura, Hiroyuki; Tsuchiya, Hiroyuki; Yachie, Akihiro (Archives of Biological Sciences, 2016)
Cyclic adenosine monophosphate (cAMP) controls differentiation in several types of cells during brain development. However, the molecular mechanism of cAMP-controlled differentiation is not fully understood. We investigated the role of protein kinase A (PKA) and exchange protein directly activated by cAMP (Epac) on cAMP-induced glial fibrillary acidic protein (GFAP), an astrocyte marker, in cultured glial cells. B92 glial cells were treated with cAMP-elevating drugs, an activator of adenylate cyclase, phosphodiesterase inhibitor and a ß adrenal receptor agonist. These cAMP-elevating agents induced dramatic morphological changes and expression of GFAP. A cAMP analog, 8-Br-cAMP, which activates Epac as well as PKA, induced GFAP expression and morphological changes, while another cAMP analog, 8-CPT-cAMP, which activates Epac with greater efficacy when compared to PKA, induced GFAP expression but very weak morphological changes. Most importantly, the treatment with a PKA inhibitor partially reduced cAMP-induced GFAP expression. Taken together, these results indicate that cAMP-elevating drugs lead to the induction of GFAP via PKA and/or Epac activation in B92 glial cells. DOI: 10.2298/ABS160112067S Key words: adenylate cyclase; Epac; GFAP; phosphodiesterase; PKA Received: January 12, 2016; Revised: February 1, 2016; Accepted: February 2, 2016; Published online: August 3, 2016 How to cite this article: Sugimoto N, Miwa S, Nakamura H, Tsuchiya H, Yachie A. Protein kinase A and Epac activation by cAMP regulates the expression of glial fibrillary acidic protein in glial cells. Arch Biol Sci. 2016;68(4):795-801.